The social world of older people - Victor, Christina R.; Scambler, Sasha Jane; Bond, John (Growing older, 2009)
Providing an account of loneliness and social isolation as experienced by older people living in Britain, this book considers the incidence and effects of isolation and loneliness, identifying the factors which lead to such experiences and considering potential interventions.